Analisis Indeks Kekeringan Menggunakan Metode Thornthwaite Mather Pada DAS Siak - Cahyono, Sandi; Suprayogi, Imam; Fauzi, Manyuk (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
The level of risk of drought in the DAS Siak can be known, by calculating the index for drought using Thornthwaite Mather method. This method emphasizes the importance of rainfall data as input and potential evapotranspiration as superficial, but it is also necessary parameters soil moisture and vegetation as listener. The relationship between rainfall and potential evapotranspiration shows the state of the showing period of drought month and and the wet month. In the drought month period the amount of rain water is not sufficient for the water used by the plant, resulting in a shortage of soil moisture. The relationship between soil moisture shortage by potential evapotranspiration yield drought index. The choice of location DAS Siak in this study in order to reinforce the Drought Disaster Risk Index Map Riau Province issued by BNPB. Climate variability analysis results showed a decrease in the average annual rainfall of 15.50 mm/yr and an increase in average annual temperature of 0.08 °C. Thornthwaite Mather method analysis results showed an increase in average drought of 3.99% every year. The highest level of risk of drought occurred in 2014 and 2015 with a duration of severe drought occurred from January to November.Keywords: drought index, Thornthwaite Mather